Spectral Studies, Corrosion Inhibition, and In Vitro Biological Investigations of Novel Synthesized Metal Complexes of (Rh+3, Pd+2, Pt+4, Au+3) with Acyclovir - Saadoun, Farah; Faisal, Mahasen (Iraqi Journal of Science, 2026)
The current study describes the synthesis of new complexes of Acyclovir ligand (AL) with heavy metal ions (Rh+3, Pd+2, Pt+4, and Au+3). These complexes were characterized by different analyses techniques, including 1H, 13C-NMR, Mass-spectra, FTIR, UV-Vis., Elemental (CHN) analysis, Flame atomic absorption spectroscopy (FAAS), the Molar conductivity, Magnetic susceptibility, and melting point measurements. The (Metal: Ligand) and Gibbs free energy for all synthesized complexes were determined by the Molar ratio method. The results of all analyses and measurement techniques gave square planar and octahedral geometries for Pd+2, Au+3, and Rh+3, Pt+4, respectively. All complexes are formed in the ratio of (1M: 2L). Acyclovir and some of its complexes behaved as inhibitors against the corrosion of carbon steel in a saline solution of NaCl (3.5%). The results showed that ligand and its complexes are effective and exhibit inhibition efficiency (IE) above 90%. On the other hand, the antibiofilm, antioxidant, and antiproliferative bioactivities of acyclovir and its complexes were investigated. The Rh(III)-complex showed the highest percentage in preventing the biofilm formation of Escherichia coli (E-Coli) at a low concentration of about 32mg/ml. In contrast, the other complexes and ligand need higher concentrations to exhibit their activity. In addition, the Rh(III)-complex showed the highest percentage in 2,2-diphenyl-1-picrylhydrazyl radical (DPPH) scavenging, followed by AL and Pt-AL. The antiproliferative activity was done versus the HFFs cancer cell line, and the Au3+-complex showed the ability to decrease the viability to about 68.27%.